Advances in Polymethine Dyes for Near‐Infrared Organic Photodiodes†. Issue 11 (2nd April 2023) - He, Jin; Xiao, Qi; Shao, Ming; Li, Zhong'an
Comprehensive Summary: Near‐infrared organic photodiodes (NIR OPDs) have tremendous potential in industrial, military, and scientific applications, due to their unique features of lightweight, low toxicity, high structural flexibility, cooling‐system‐free, etc . However, the overall performance of currently available NIR OPDs still lags behind the commercial inorganic photodetectors, ascribed to the critical challenge of realizing organic semiconductors with sufficiently low optical bandgap and excellent optoelectronic properties simultaneously. Among various types of NIR‐absorbing organic semiconductors, polymethine dyes not only possess advantages of simple synthesis and structural diversity, but also show fascinating optical and aggregation features in the solid state, making them attractive material candidates for NIR OPDs. In this review, after a brief introduction of NIR OPDs and polymethine dyes, we comprehensively summarize the advances of polymethine dyes for broadband and narrowband NIR OPDs, and further introduce their applications in all‐organic optical upconversion devices and photoplethysmography sensors. In particular, the relationship between the chemical structure and the aggregation behaviors of polymethine dyes and the device performance is carefully discussed, providing some important molecular insights for developing high performance NIR OPDs. Abstract : This review gives a comprehensive summary of polymethine dyes for broadband and narrowband near‐infrared organic photodetectors, as well as their applications in all‐organic optical upconversion devices and photoplethysmography sensors. Particularly, the relationship between chemical structure and aggregation behaviors of polymethine dyes and the device performance has been discussed carefully.